Tobacco smoking initiation among students in Samoa and health concerns. - Baljeet Singh (Public Library of Science (PLoS), 2021)
Background High prevalence of tobacco smoking among young students remains a serious health concern given the positive association between smoking and NCDs. More recently, some studies also noted young smokers were more likely to get infected with COVID-19 compared to non-smokers. This study aims to assess the factors that influence smoking uptake among young students in Samoa. Findings from this study will provide valuable insight to policymakers and health authorities on policies and strategies to combat smoking among youth in Samoa and the Pacific Island Countries (PICs). Methods The 2017 Global Youth Tobacco Survey data of Samoa, available from the World Health Organization is used in the analysis. We use the multinominal logistic model to investigate the effects of socio-economic and demographics factors on young students' uptake of smoking in Samoa. Result The main findings of this study indicate that sex, age, friendship, parental smoking, family discussion, outside influence, pocket money, and mother's education are important determinants of tobacco smoking initiation among youths in Samoa. Conclusion Our findings contribute towards the evidence of the imperative health impact of friends, parents, and public smoking on students in Samoa. This warrants strategies that are effective in discouraging parents from smoking and implement measures that prevent smoking in public places. Moreover, educational efforts, particularly those that encourage more discussion at home settings on the harmful effects of smoking are strongly recommended. Parents are strongly encouraged to regularly monitor children's spending behaviour.